2015
DOI: 10.1088/1475-7516/2015/10/037
|View full text |Cite
|
Sign up to set email alerts
|

Conformal invariant cosmological perturbations via the covariant approach

Abstract: It is known that some cosmological perturbations are conformal invariant. This facilitates the studies of perturbations within some gravitational theories alternative to general relativity, for example the scalar-tensor theory, because it is possible to do equivalent analysis in a certain frame in which the perturbation equations are simpler. In this paper we revisit the problem of conformal invariances of cosmological perturbations in terms of the covariant approach in which the perturbation variables have cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Since the adiabatic perturbations are invariant under conformal transformation [66][67][68][69][70][71][72][73][74], the relationships between observable n s and r in different frames are easily established although the physical equivalence between Einstein and Jordan frames is unclear [75][76][77][78][79]. To reconstruct the potential V J [ψ(φ )] in the Jordan frame, we need to have the relation between the potentials in different frames.…”
Section: The Reconstruction Methodsmentioning
confidence: 99%
“…Since the adiabatic perturbations are invariant under conformal transformation [66][67][68][69][70][71][72][73][74], the relationships between observable n s and r in different frames are easily established although the physical equivalence between Einstein and Jordan frames is unclear [75][76][77][78][79]. To reconstruct the potential V J [ψ(φ )] in the Jordan frame, we need to have the relation between the potentials in different frames.…”
Section: The Reconstruction Methodsmentioning
confidence: 99%
“…Thus though this result is actually a reflection that the perturbations are conformal invariant fully nonperturbatively, 1 e.g. [26,27], it may offer us a different angle of view to the inflation scenario itself and also the primordial universe.…”
Section: Jhep03(2016)134mentioning
confidence: 96%
“…In this spirit, primordial fluctuations in various scalar-tensor theories have been discussed in refs. [24][25][26][27][28][29][30][31][32][33], where it has been observed that a scale invariant spectrum is compatible with slow expansion.…”
Section: Jcap05(2016)041mentioning
confidence: 99%